Impact of different pack sizes of paracetamol in the United Kingdom and Ireland on intentional overdoses: a comparative study. - Hawton, K; Bergen, H; Simkin, S; Arensman, E; Corcoran, P; Cooper, J; Waters, K; Gunnell, D; Kapur, N (BioMed Central, 2011)
BACKGROUND: In order to reduce fatal self-poisoning legislation was introduced in the UK in 1998 to restrict pack sizes of paracetamol sold in pharmacies (maximum 32 tablets) and non-pharmacy outlets (maximum 16 tablets), and in Ireland in 2001, but with smaller maximum pack sizes (24 and 12 tablets). Our aim was to determine whether this resulted in smaller overdoses of paracetamol in Ireland compared with the UK. METHODS: We used data on general hospital presentations for non-fatal self-harm for 2002-2007 from the Multicentre Study of Self-harm in England (six hospitals), and from the National Registry of Deliberate Self-harm in Ireland. We compared sizes of overdoses of paracetamol in the two settings. RESULTS: There were clear peaks in numbers of non-fatal overdoses, associated with maximum pack sizes of paracetamol in pharmacy and non-pharmacy outlets in both England and Ireland. Significantly more pack equivalents (based on maximum non-pharmacy pack sizes) were used in overdoses in Ireland (mean 2.63, 95% CI 2.57-2.69) compared with England (2.07, 95% CI 2.03-2.10). The overall size of overdoses did not differ significantly between England (median 22, interquartile range (IQR) 15-32) and Ireland (median 24, IQR 12-36). CONCLUSIONS: The difference in paracetamol pack size legislation between England and Ireland does not appear to have resulted in a major difference in sizes of overdoses. This is because more pack equivalents are taken in overdoses in Ireland, possibly reflecting differing enforcement of sales advice. Differences in access to clinical services may also be relevant.